Intensi adopsi e-commerce dan aplikasi sistem akuntansi - Ferry Kosadi; Rama Chandra Jaya; Deni Hamdani (Universitas Negeri Malang, 2021)
AbstractThe purpose of this research is to analyze behavioral intention to conduct online selling and adopt accounting applications, and its effect on the actual use. The research was conducted from the planning and online selling processes through e-commerce platform to the preparation of financial reports by application to measure the intention to adopt and the actual usage of information technology. The study indicates that actual usage of accounting technology is influenced by intention to adopt, with the main factors consisting of the compatibility and observability of the technology. Complexity, relative advantage, and triability are not the obstacles to adopt the accounting technology as long as the technology is userfriendly and easy to observe. Awareness of the importance of accounting information system application and the difficulty of manual accounting processes is the driver of the intention to adopt accounting technology. There are good opportunities to increase digital literacy skills through technology diffusion, which is focused on transforming business technology along with material adjustments and eliminating inhibiting factors such as difficulties in accessing digital devices and their usage.AbstrakPenelitian ini bertujuan untuk menganalisis minat melakukan online selling dan mengadopsi aplikasi akuntansi serta pengaruhnya terhadap penggunaan sebenarnya. Penelitian dilakukan dari proses perencanaan dan online selling pada platform e-commerce hingga penyusunan laporan keuangan yang menggunakan aplikasi untuk mengukur minat adopsi dan actual usage dari teknologi informasi. Hasil penelitian menunjukkan bahwa actual usage teknologi akuntansi dipengaruhi oleh adanya minat untuk mengadopsi dengan faktor utama berupa kompatibilitas dan observabilitas dari teknologi akuntansinya. Faktor kompleksitas, keunggulan relatif, dan triability tidak menjadi halangan untuk mengadopsi penggunaan teknologi akuntansi selama sesuai dengan kondisi penggunanya dan mudah untuk diobservasi. Kesadaran terkait pentingnya adopsi teknologi akuntansi dan kesulitan proses akuntansi secara manual menjadi bagian dalam minat mengadopsi aplikasi sistem informasi akuntansi. Terdapat peluang yang baik untuk peningkatan kemampuan literasi digital melalui difusi teknologi yang berfokus pada transformasi teknologi bisnis disertai penyesuaian materi serta menghilangkan faktor penghambat seperti kesulitan akses pada perangkat digital dan pemanfaatannya.